Microbial Community Structure and Functionality in the Deep Sea Floor: Evaluating the Causes of Spatial Heterogeneity in a Submarine Canyon System (NW Mediterranean, Spain) - Román, Sara; Ortiz-Álvarez, Rüdiger; Romano, Chiara; Casamayor, Emilio O.; Martin, Daniel (Frontiers in Marine Science, 2019)
Understanding community assembly and processes driving diversity in deep-sea environments is a major challenge in marine microbial ecology. The deep sea represents the largest ecosystem on Earth, but its remoteness makes the microbial community composition and functionality largely unknown. Moreover, microbial-focused studies comparing different deep-sea habitats like dynamic submarine canyons and slope ecosystems altogether are rare. The present work aims to study the deep-sea seafloor microbial communities (Bacteria and Archaea) of the Blanes Canyon and its adjacent western open slope (NW Mediterranean) at ca. 1500 m deep, in autumn and spring, and along the vertical sediment profile. Microbial assemblages were studied in terms of abundance, diversity (α and β), community structure and functional potential through 16S rRNA tag-sequencing to assess their adaptations to the canyon’s idiosyncrasy. Furthermore, the relationships of microbes with environmental variables and a potential predator (nematodes) were also assessed. We observed overall marked differences between canyon and open slope microbial assemblages, although their phyla composition was similar. Both the dominant and richest phyla showed significant differences in proportion between canyon and slope. Bacterial diversity was higher in the canyon than in the open slope, together with nematode abundances. Microbial assemblages were more heterogeneous and showed a higher temporal variability in the canyon than in the open slope. Microbial abundances along the vertical sediment profile showed high heterogeneity in the canyon while on the slope consistently decreased with depth. Nematode and microbial abundances were correlated in the more stable slope environments, while in the canyon phytodetritics inputs (Chl a and Chl a: phaeo) and organic carbon seem to play a role in controlling microbial diversity and abundance. Grain size was correlated with microbial abundances and explained part of the variability in the community structure. Predicted functional profiles differed per habitat and sediment layer, and specific metabolisms appear to be distinctively enhanced, such as aerobic pathways in the most superficial sediment layers in the canyon. Overall, we observed specific patterns of nutrient inputs, microbial composition, and predicted functionality, which may affect higher trophic levels (i.e, Meiofaunal nematodes). This study highlights the importance of canyon heterogeneity in shaping microbial communities.